Tricuspid and pulmonary valve endocarditis associated with double-chambered right ventricle - Myeong, Jin Cheol; Chin, Jung Yeon; Choi, Jin Ho; Rah, Young Min; Park, Jun Hyung (Kosin Medical Journal (Online), 2015)
We report a rare case of tricuspid valve and pulmonary valve endocarditis associated with a double-chambered right ventricle in an adult female with pulmonary artery aneurysm and septic pulmonary embolism by Streptococcus mitis. She was treated with aggressive antibiotic therapy followed by debridement of the infective lesion of tricuspid valve, pulmonary valve replacement using xenograft and resection of obstructing muscular bundles in right ventricle.